STRATEGI PENGEMBANGAN DESA MENUJU DESA MANDIRI (Studi di Desa Tumbuk Tebing Kecamatan Bunga Mas Kabupaten Bengkulu Selatan) - Rahiman Dani; Donny Cristofer Sagala; Henny Aprianty (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2026)
This study aims to examine the actual conditions, local potential, and development strategies in promoting village self-reliance in Tumbuk Tebing Village based on the Village Development Index (Indeks Desa Membangun/IDM). The analysis focuses on three key dimensions of IDM, namely social resilience, economic resilience, and environmental resilience. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and documentation. The informants consist of village government officials, community leaders, and local residents who are directly involved in village development activities. The findings reveal that the social resilience of Tumbuk Tebing Village is relatively strong, as indicated by improved access to education and health services, as well as active community participation in social and institutional activities. Meanwhile, economic resilience is in a developing stage, supported by agriculture, plantations, micro-enterprises, and village-owned enterprises (BUMDes), although management and sustainability still require improvement. In contrast, environmental resilience is generally well maintained through basic waste management, clean water availability, and community-based environmental activities, yet it remains limited and not fully integrated into a systematic framework. Furthermore, the study reveals that the village government's development strategies include strengthening social services, supporting local economic activities, enhancing infrastructure, and promoting environmental management. However, these strategies tend to be sectoral and not fully integrated. Therefore, future development efforts should focus on enhancing human resource capacity, optimizing local economic potential, strengthening institutional capacity, and implementing sustainable and participatory environmental management. In conclusion, Tumbuk Tebing Village has strong foundational potential to achieve village self-reliance. Nevertheless, an integrated and sustainable development strategy across social, economic, and environmental dimensions is essential to improve its IDM status and achieve a more independent and resilient village.